Being smart or getting smarter: Implicit theory of intelligence moderates stereotype threat and stereotype lift effects. (27th April 2016) - Froehlich, Laura; Martiny, Sarah E.; Deaux, Kay; Goetz, Thomas; Mok, Sog Yee
Abstract : This research explores implicit theory of intelligence (TOI) as a moderator of stereotype activation effects on test performance for members of negatively stereotyped and of favourably stereotyped groups. In Germany, Turkish‐origin migrants are stereotyped as low in verbal ability. We predicted that on a test diagnostic of verbal intelligence, endorsement of an entity TOI predicts stereotype threat effects for Turkish‐origin students and stereotype lift effects for German students. This effect could account for some of the performance gap between immigrants and host society members after stereotype activation. Study 1 ( N = 107) established structural equivalence of implicit theories across the ethnic groups. In two experimental studies (Study 2: N = 182, Study 3: N = 190), we tested the moderating effect of TOI in a 2 (stereotype activation: diagnostic vs. non‐diagnostic test) × 2 (ethnicity: German vs. Turkish migration background) experimental design. The results showed that when the test was described as diagnostic of verbal intelligence, higher entity theory endorsement predicted stereotype threat effects for Turkish‐origin students (Study 2 and Study 3) and stereotype lift effects for German students (Study 3). The results are discussed in terms of practical implications for educational settings and theoretical implications for processes underlying stereotype activation effects.